The FRED flow-diverter stent for intracranial aneurysms: clinical study to assess safety and efficacy - Möhlenbruch, Markus Alfred; Herweh, Christian; Jestaedt, Leonie; Stampfl, Sibylle; Schönenberger, Silvia; Ringleb, Peter A.; Bendszus, Martin; Pham, Mirko (American journal of neuroradiology, 2015)
BACKGROUND AND PURPOSE: Flow-diverter stents are emerging for the endovascular treatment of difficult-to-treat or otherwise untreatable cerebral aneurysms (wide-neck, fusiform, dissecting, blisterlike, or giant). We assessed the clinical safety and efficacy of the Flow-Redirection Endoluminal Device. - MATERIALS AND METHODS: This was an institutional review board-approved single-center observational clinical study in 29 patients with 34 aneurysms elected to be treated by endovascular intervention. After providing informed consent, patients were included according to the following criteria: aneurysm fundus-to-neck ratio <2 or neck diameter >4 mm, fusiform, dissecting, or giant aneurysms. The primary end point for clinical safety was the absence of death, absence of major or minor stroke, and absence of transient ischemic attack. The primary end point for treatment efficacy was complete angiographic occlusion according to the O'Kelly Marotta grading scale immediately after the procedure and at follow-up after 3 and 6 months (O'Kelly Marotta D: complete occlusion). - RESULTS: The Flow-Redirection Intraluminal Device deployment was technically successful in all cases. In 26/29 (89%) of patients, the primary end point of safety was reached; in the 3 remaining patients, 1 disabling ischemic stroke and 2 minor strokes with complete recovery at follow-up were observed. Angiographic (DSA and MRA) and clinical follow-up were available after 3 months in 29/29 (100%) and after 6 months in 25/29 (86%) patients (after 6 months, only MRA follow-up was performed according to our study protocol and institutional standard). At 3-month follow-up, complete occlusion was reached in 19/34 aneurysms (O'Kelly Marotta D: 19/34; 56%). At 6-month follow-up, aneurysm occlusion was complete in 22/30 aneurysms (O'Kelly Marotta D: 22/30; 73%). - CONCLUSIONS: Deployment of the Flow-Redirection Intraluminal Device flow-diverter stent is safe and effective in the treatment of difficult-to-treat or otherwise untreatable intracranial aneurysms.
Gesehen am 08.06.2020